Total synthesis and anticancer activity of the natural oleanolic acid bidesmoside saponin, albidoside A, isolated from the roots of Acacia albida. Issue 1 (January 2020) - Guo, Tiantian; Song, Yiming; Lu, Yinghui; Li, Guolin; Liu, Tian; Han, Wenrong; Song, Weiguo; Yang, Chuncheng; Li, Fahui; Liu, Qingchao
The first synthesis of a natural triterpenoid saponin bearing N -acetylglucosamine, albidoside A, which is isolated from the roots of Acacia albida, is concisely achieved in a convergent strategy. Preliminary pharmacological research shows anticancer activity against HL-60, MCF-7, MDA-MB-231, Hep-2, and Hela cell lines. In particular, it exhibited good selectivity, which is five times more cytotoxic toward Hep-2 cells (IC50  = 8.91 μM) than the Hela cell line.